Enhancing dopaminergic signaling and histone acetylation promotes long-term rescue of deficient fear extinction - Whittle, N (Transl Psychiatry, 2016)
Extinction-based exposure therapy is used to treat anxiety- and trauma-related disorders; however, there is the need to improve its limited efficacy in individuals with impaired fear extinction learning and to promote greater protection against return-of-fear phenomena. Here, using 129S1/SvImJ mice, which display impaired fear extinction acquisition and extinction consolidation, we revealed that persistent and context-independent rescue of deficient fear extinction in these mice was associated with enhanced expression of dopamine-related genes, such as dopamine D1 (Drd1a) and -D2 (Drd2) receptor genes in the medial prefrontal cortex (mPFC) and amygdala, but not hippocampus. Moreover, enhanced histone acetylation was observed in the promoter of the extinction-regulated Drd2 gene in the mPFC, revealing a potential gene-regulatory mechanism. Although enhancing histone acetylation, via administering the histone deacetylase (HDAC) inhibitor MS-275, does not induce fear reduction during extinction training, it promoted enduring and context-independent rescue of deficient fear extinction consolidation/retrieval once extinction learning was initiated as shown following a mild conditioning protocol. This was associated with enhanced histone acetylation in neurons of the mPFC and amygdala. Finally, as a proof-of-principle, mimicking enhanced dopaminergic signaling by L-dopa treatment rescued deficient fear extinction and co-administration of MS-275 rendered this effect enduring and context-independent. In summary, current data reveal that combining dopaminergic and epigenetic mechanisms is a promising strategy to improve exposure-based behavior therapy in extinction-impaired individuals by initiating the formation of an enduring and context-independent fear-inhibitory memory.